Home-schooling During the Two-year COVID-19 Lockdown in Uganda: A Critical Analysis - Milliam, Kiconco; Dominic, Karyarugokwo (Advances in Social Sciences Research Journal, 2022)
In writing this paper, we have used secondary review methodology to critically analyse home-schooling in Uganda during the two-year COVID-19 school lockdown. This paper has used data from articles, newspapers, government documents and Non-Governmental Organizations reports. The paper begins with a discussion of the history of home-schooling and how countries resorted to home-schooling to curb the spread of corona virus. This is followed by a section that discusses Uganda's COVID-19 response and home-schooling in Uganda during the COVIDD-19 pandemic. Then, is the discussion about the limitations of home-schooling in Uganda. This section shows that much as the government of Uganda implemented a well-intentioned home-schooling program during the two-year school lockdown, most of the children, especially, those from poor families did not benefit because of factors such as lack of access to electronic gadgets, lack of internet, failure to receive self-study materials and lack of parental guidance among other factors. The paper ends with the conclusion that emphasises the view that much as all primary and secondary school-going children received an automatic promotion to the next class when the schools were re-opened in January 2022, the educational inequality between the children of the poor and the rich that was widened during the two-year COVID-19 lockdown will have a long-lasting negative implication on the learning outcomes of, especially, the children from the poor backgrounds.